The diffusion and dynamics of producer prices, deflationary pressure across Asian countries, and the role of China - Hongyi Chen; Michael Funke; Andrew Tsang (Bank of Finland, Institute for Economies in Transition (BOFIT), 2016)
​Persistent producer price deflation in China and other Asian economies has become a genuine concern for policymakers. In June 2016, China's producer prices were down 12.7 percent from their peak in 2011, following a 52-month stretch of consecutive negative producer price readings (March 2012 to June 2016). Given problems with overcapacity and heavy corporate debt burdens, the incessant decline in producer prices has eroded corporate profitability, dampened fixed in-vestment and depressed growth overall. This paper analyzes the determinants of producer price declines across eleven Asian economies, finding that the recent synchronous and protracted pro-ducer price deflation has been driven by weak production growth, low commodity prices, spill-over effects from China, and, to a lesser extent, exchange rate pass-through. With China at the heart of the region's producer price deflation challenge, we consider the structural adjustments needed in China to cope with the decline and head off deflationary threats.
URN:NBN:fi:bof-201609141411
Keywords: C23; C32; E31; 330